A multimedia learning system for Malaysian novice drivers - Foo, Esther Hui Hui (University Malaysia Sarawak, (UNIMAS), 2010)
This study aims to create a multimeaia learning system for Malaysian novice drivers to learn about traffic rules and regulation. This involves developing and integrating various' media to produce the multimedia system to overcome some limitations ob~rved in current text and image-based textbook. This study is targeted at Malaysian novice drivers aged from 17 years old and above who wanted to obtain their driving license. The content scope of this study is taken from two sub-topic in "Kurikulum Pendidikan Pemandu" textbook which are "Olahgerak" and "Peraturan di Pelbagai Persimpangan". Multimedia is used to design and develop the system, which involve incorporating audio, graphics, videos and text to represent the selected contents from KPP text book. The overall" system can €also be presented on the web.